USAHA PENINGKATAN PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (Cucumis Sativa L.) MELALUI APLIKASI KOMPOS LIMBAH PASAR DAN PEREMPELAN DAUN - Ryan Firman Syah; M. Rifki Lidra Pratama; Yohana Theresia Maria Astuti (Partner, 2023)
The research aims to determine the best dosage of market waste compost and the best leaf pruning in growth and production of cucumber. The research design used a complete factorial randomized design consisting of 2 factors. The first factor is the dose of market waste compost (K) consisting of namely control, 75 g, 100 g, and 125 g. The second is leaf pruning (P) consisting of namely control, 6 leaves, 8 leaves, and 10 leaves. The data were analyzed using Duncan's Multiple Range Test (DMRT). The results showed no significant interaction between the organic fertilizer and leaf pruning on growth and yield of cucumber. A dose of 75 g of organic fertilizer was sufficient to significantly improve the growth and yield of cucumber, while doses of 125 g and 100 g had the same effect. Leaf pruning significantly affected fresh weight parameters and the fresh weight of cucumber roots. Key Words: market waste compost, leaf pruning, cucumber